THE EFFECTS OF COUPLING AGENT AND SURFACE TREATMENT ON MORPHOLOGICAL AND MECHANICAL PROPERTIES OF KENAF FIBER REINFORCED POLYPROPYLENE COMPOSITES - , HENNY PRATIWI; , Ir. R. Soekrisno, MSME., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of high -performance engineering products made from natural resources is increasing worldwide, due to renewable and environmental issues. Among the many different types of natural resources, kenaf plants have been extensively exploited over the past few years. However, the hydrophilic nature of fiber is the main challenge for the use of natural fiber in plastic which could cause the poor compatibility between fiber and matrix. Chemical treatment is considered to modify the fiber surface properties. In this study, kenaf bast fibers were treated with various concentrations of NaOH with different immersed time, immersed temperature, and dried temperature. The analysis of variance (ANOVA) shows that the most Fiber bundle tensile were performed to evaluate the effect of treatments on the fiber tensile strength. Taguchi Methods are used in order to obtain the optimal parameter which could affect the tensile strength of kenaf fibers. The L9 (34) Four-Parameter, Three-Level Orthogonal array is used to design the experiment. Experimental results reveal that the chemical treatment of fibers has modified the fiber surface and increased the fiber strength. significant alkali parameter is NaOH concentration, which accounts for 54% of the total, followed by drying temperature (22%), the immersed time and immersed temperature only account for 19% and 6% respectively. It is also found that the optimum treatment is kenaf immersed in 3 wt.% NaOH solution for 1 hour at 33oC and dried at 60oC. Fourier transform infrared spectroscopy analysis also shows the same result. On the other hand, the scanning electron microscopy examination reveals that fiber surface immersed in NaOH at 100oC has the better surface than at 33oC. The effects of t A fiber content of 50% wt.% has been proven to provide adequate reinforcement to increase the strength of the polypropylene sheet. The optimum alkali treatment and fiber content then used as parameters for composite manufacturing with the addition of 2 different concentrations of MAPP. hese chemical treatment and addition on the tensile, flexural, impact and water absorption properties of the composites were investigated. Mechanical test results show that alkali treatment followed by MAPP addition significantly improves the mechanical properties of short fibre non-woven kenaf polypropylene composites. The better bonding between fiber and matrix is resulted by the alkali treatment and the use of a coupling agent, 5% polypropylene-graft-maleic anhydride enabled successful fiberâmatrix adhesion.